KAJIAN TOKSISITAS DARI TUBUH BUAH Ganoderma lucidum DENGAN METODE BRINE SHRIMP LETHALITY TEST (BST) - Ross Nurul Rohmah; Nuniek Ina Ratnaningtyas; Ari Asnani (Scripta Biologica, 2014)
Ganoderma lucidum is polyporus fungi from Basidiomycetes which can be used as traditional medicines. Toxicity test with Brine Shrimp Lethality Test (BST) method using Artemia salina was conducted to find out toxic effect of G.lucidum. An extract would have toxic effect if the LC50 < 1000 µg/ml. The aims of this experiment were to know about the toxicity level from G.lucidum with Brine Shrimp Lethality Test (BST) method and determined the concentration of fruiting body extract of G.lucidum which had the best toxicity effect in LC50. There were two extraction methods used in this experiment, first one stage extraction and then multilevel extraction with hexane, ethyl acetate, and ethanol. Each solvent was made in 1000 ppm, 500 ppm, 250 ppm, and 125 ppm. This process was repeated for three times. This experiment used G.lucidum extract which was tested to A.salina and secunder compound metabolit test from the most toxic G. lucidum was done with phytochemical analysis. The result indicated that fruiting body extract from G.lucidum could kill A.salina because all extract was positively contained alkaloid and terpenoid but negatively contained flavonoid. Fruiting body extract from G.lucidum which had lowest LC50 wass ethyl asetat extract with one stage extraction in concentration 53,70 ppm and highest LC50 was ethanol extract with multilevel extraction in concentration 501,18 ppm.